Is the Food Insecurity Experiences Scale (FIES) A Valid Tool for Assessing Food Insecurity in Sudan? - S. Mohamed Abdalla, Samar (Jordan Journal of Agricultural Sciences, 2024)
Food insecurity is a widespread issue globally, and the Food and Agriculture Organization (FAO) developed the Food Insecurity Experience Scale (FIES) to measure different levels of food insecurity severity. The FIES includes eight questions that assess people's access to sufficient and quality food. This study aims to examine the reliability and validity of using the FIES as a measurement tool for food insecurity and to provide guidance for policymakers to address hunger and ensure food security in Sudan. A sample of 330 households from the White Nile State in Sudan was chosen to complete the FIES questionnaire. The collected data was then analyzed using descriptive statistics, Alpha Cronbach’s, and exploratory factor analysis (EFA). The FIES results indicate that approximately 33.6% of households are moderately affected by food insecurity, while 37.9% experience severe food insecurity. The Alpha Cronbach’s coefficient confirms that the FIES questions display acceptable internal consistency. Moreover, the EFA results reveal two main components that account for about 60.7% of the total variance in the FIES questions. Consequently, this study recommends the FIES as a reliable and valid tool for assessing food insecurity in Sudan